2014
DOI: 10.1016/j.jss.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond survival as a measure of success: understanding the patient experience of necrotizing soft-tissue infections

Abstract: Background Necrotizing Soft Tissue Infections (NSTIs) represent a devastating spectrum of disease with high case-mortality and resource intensive care. Treatment consists of wide surgical debridement and often prolonged periods of ICU care. Major complications are common. The severity of the disease and the aggressive treatment requirements put survivors at risk for significant long-term sequelae related to the trauma of both disease and treatment. Information about the post-discharge impact of NSTIs on surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
3
28
1
Order By: Relevance
“…32 The HRQoL after NSTIs has only been assessed in four prior studies (one qualitative and three quantitative studies with respectively 4.2, 3.2, 4.1, and 5 years follow-up and similar sample sizes ranging from 19 to 56 participants). 14,[33][34][35] The biggest differences between these studies and ours are either the study design (qualitative versus quantitative) or the study population (NSTI of all body regions vs. upper score for NSTIs affecting all body regions are lower than the scores found in our study specifically assessing NSTIs of the upper extremity, which were respectively 80.0, 48.7, and 55.3. Based on this comparison, it could be hypothesized that NSTIs of the upper extremity have less consequences for the eventual HRQoL compared with NSTIs affecting other body regions.…”
Section: Discussioncontrasting
confidence: 74%
“…32 The HRQoL after NSTIs has only been assessed in four prior studies (one qualitative and three quantitative studies with respectively 4.2, 3.2, 4.1, and 5 years follow-up and similar sample sizes ranging from 19 to 56 participants). 14,[33][34][35] The biggest differences between these studies and ours are either the study design (qualitative versus quantitative) or the study population (NSTI of all body regions vs. upper score for NSTIs affecting all body regions are lower than the scores found in our study specifically assessing NSTIs of the upper extremity, which were respectively 80.0, 48.7, and 55.3. Based on this comparison, it could be hypothesized that NSTIs of the upper extremity have less consequences for the eventual HRQoL compared with NSTIs affecting other body regions.…”
Section: Discussioncontrasting
confidence: 74%
“…Early data showed that survivors of NSTI had decreased HRQOL and significant impairments in physical, emotional, and social functioning. 82,84 There is also an increased prevalence of PTSD in both the patient and their partners. A large proportion of survivors are unable to return to previous employment.…”
Section: In-hospital and Long-term Outcomesmentioning
confidence: 99%
“…HRQoL is defined as an individual's or a group's perceived physical health and mental health (MH) over time. 12 Described physical consequences of NSTI include scar problems (pain, itching, decreased mobility) 13,14 and loss of energy. 15 Many mental consequences have been described.…”
Section: Introductionmentioning
confidence: 99%